Poverty, Exploitation, and Survival: The Reality of Migrant Workers in Informal Sector of Bangladesh - Islam, Md. Zahidul (Universitas Muhammadiyah Ponorogo, 2025)
Child violence is a critical issue within the 2030 Sustainable Development Goals, requiring a collaborative approach among agencies for effective management. This study examines the collaborative governance processes implemented by the South Sumatra Provincial Women's Empowerment and Child Protection Agency, the South Sumatra Regional Police, the Class I Palembang Correctional Service, and the Class I Palembang Child Correctional Institution. Utilizing a qualitative methodology, this research gathered primary and secondary data through observation, interviews, and documentation. Analysis based on the collaboration process theory by Ansell & Gash (2008) indicates that collaborative governance has been effective, characterized by face-to-face dialogue, trust-building, joint commitment, and shared understanding, as well as the achievement of interim results. However, improvements are needed in inter-agency communication and the development of Standard Operating Procedures (SOP) for handling child violence cases, to strengthen the collaborative process and achieve sustainable outcomes.